2018
DOI: 10.24093/awej/vol9no1.2
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of WhatsApp on EFL students' Vocabulary Learning

Abstract: Social networking applications have emerged as potential new tools for enhancing second language vocabulary learning. The current study explores the development of academic vocabulary knowledge of English as a foreign language (EFL) students using WhatsApp compared to the traditional method of vocabulary instruction. It also aims at investigating students' perceptions about the use WhatsApp in learning vocabulary. Forty Arab EFL students at the elementary level enrolled at a public university in the Arabian Gu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
69
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(76 citation statements)
references
References 0 publications
4
69
0
3
Order By: Relevance
“…Based on the social interaction occurred in the WhatsApp group, the pupils then constructed their own meaning and understanding on the accurate vocabulary that should be used in the narrative writing which then reflects the cognitive constructivism theory of learning, as the progress shown 75% of the pupils proved that they have developed a significant understanding in constructing their narrative writing. This is in line with the study by Bensalem (2018) as WhatsApp mediation is perceived effective than traditional instruction in enhancing learners' vocabulary learning thus, reflects the constructivist theory since WhatsApp has helped students construct their vocabulary knowledge. Apart of that, the progress displayed by the pupils also reflects the ZPD theory in which the tasks that the pupils could not do by themselves were accomplished through the assistance and feedback received from the teacher-researcher, other members in the WhatsApp group as well as the resources available such as the dictionary app on the appropriate vocabulary that should be used in the narrative writing.…”
Section: Post-testsupporting
confidence: 88%
“…Based on the social interaction occurred in the WhatsApp group, the pupils then constructed their own meaning and understanding on the accurate vocabulary that should be used in the narrative writing which then reflects the cognitive constructivism theory of learning, as the progress shown 75% of the pupils proved that they have developed a significant understanding in constructing their narrative writing. This is in line with the study by Bensalem (2018) as WhatsApp mediation is perceived effective than traditional instruction in enhancing learners' vocabulary learning thus, reflects the constructivist theory since WhatsApp has helped students construct their vocabulary knowledge. Apart of that, the progress displayed by the pupils also reflects the ZPD theory in which the tasks that the pupils could not do by themselves were accomplished through the assistance and feedback received from the teacher-researcher, other members in the WhatsApp group as well as the resources available such as the dictionary app on the appropriate vocabulary that should be used in the narrative writing.…”
Section: Post-testsupporting
confidence: 88%
“…Moreover, the interview revealed that students experienced emotions of happiness, pride, and joy from using the WhatsApp application in the experiment (Çam & Can, 2019). The correlation between WhatsApp and students' motivation in language learning/teaching has also been reviewed in many studies (Alamer, 2016;Bensalem, 2018;Han & Keskin, 2016;Khan, 2016). Motivation can be defined as 'the set of thoughts and feelings that create a person's interest to do something' (Alnakeeb, 2012:19).…”
Section: Whatsapp's Effect On Students' Attitudes Motivation and Anxmentioning
confidence: 99%
“…Fattah (2015) surmises that the experimental group benefited from using the WhatsApp group. Bensalem (2018), however, focuses on the effect of WhatsApp on improving the learners' capacity in English vocabularly. He conducted a six-week experimental research program to explore the impact of using a WhatsApp group on learning vocabulary in English with 40 undergraduates in a Saudi Arabian university.…”
Section: English As L2 On Social Media In Saudi Arabiamentioning
confidence: 99%
“…The studies conducted by Fattah (2015), Kutbi (2015), Ahmed (2016) were limited by the use of social media in relation to teaching a specific English language course to undergraduate students majoring in English. Fattah (2015) and Ahmed (2016) replaced the classroom walls with a group via social media to deliver English learning materials in their experimental groups of participants while Kutbi (2015) and Bensalem (2018) supplemented a faceto-face course with social media. Alnujaidi's (2017) study, however, explored the views of undergraduate students of both genders, doing various majors, regarding using social media to offer English language learning materials.…”
Section: English As L2 On Social Media In Saudi Arabiamentioning
confidence: 99%